Essentials of Pericyclic and Photochemical Reactions - Dinda, Biswanath (Springer International Publishing : Imprint: Springer, 2017)
This book provides a concise introduction to pericyclic and photochemical reactions for organic synthesis. In the first part about pericyclic reactions, the author explains electrocyclic reactions, cycloaddition reactions, sigmatropic rearrangements, and group transfer reactions. The second part on photochemistry is dedicated to photochemical reactions of a variety of compound classes, including alkenes, dienes, and polyenes, carbonyl compounds, and aromatic compounds. Additionally, photofragmentation reactions are described in a dedicated chapter. The last chapter gives an outlook on applications of photochemistry and natural photochemical phenomena. Both parts start with a comprehensive presentation of the general principles of the pericyclic and photochemical reactions. All chapters are rich in examples, which help illustrate the explained principles and establish ties to results and trends in recent research. Additionally, each chapter offers exercises for students, and solutions to the problems are provided in a separate appendix. This book nicely illustrates the utility of pericyclic and photochemical reactions and provides students and researchers with the tools to apply them routinely for an efficient synthesis of complex organic molecules. It will therefore appeal to advanced undergraduate students, graduate and postgraduate students, and even to practitioners and scientists in the field of organic synthesis. The rich examples and exercises will also make it a versatile tool for teachers and lecturers.- Resumé vydavatel
Keywords: organická chemie; fyzikální chemie; fotochemie; organic chemistry; physical chemistry; photochemistry; elektronické knihy; monografie; electronic books; monographs